2018
DOI: 10.14198/jhse.2018.133.06
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of selected physical fitness parameters in Olympic clay target shooting

Abstract: Purpose: To examine the current state of empirical research, theoretical explanations and applied importance of selected physical fitness parameters in Olympic clay target and related shooting disciplines. Method: Four online databases (EBSCOhost, Pub Med, Emerald Insight and Google Scholar) served as data sources for the study. Multiple combinations of key terms (e.g., shooting sport, skeet, and trap) were used to identify relevant literature in the English language meeting pre-specified search criteria. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Another possible explanation for the absence of rifle performance differences could be that physical demands are smaller in shooting than in other sports [4]. Consequently, skills like movement accuracy and coordination could be key factors in shooting [32,33], specifically when balance seems to play a stronger role in rifle than in pistol events [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation for the absence of rifle performance differences could be that physical demands are smaller in shooting than in other sports [4]. Consequently, skills like movement accuracy and coordination could be key factors in shooting [32,33], specifically when balance seems to play a stronger role in rifle than in pistol events [34].…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this finding could be in the use of different weapons. A pistol requires shoulder and grip strength [38,39], while a rifle requires balance skills [32,40]. This implies that the younger rifle shooters in the senior category compete under lower physical demands regardless of the maturational development associated with chronological age.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our research deepens the scientific information on the need to take into account the athletesshooters' physical conditioning indices during the training process (Polyakov M., 1982;Maglovanyy A., Pazichuk O., 2012;Wagner P., 2012;Sobko I., 2012;Peljha Z., Michaelides M., Collins D., 2018).…”
Section: Discussionmentioning
confidence: 84%
“…The script included open questions related to several knowledge topics according to the existing scientific literature [19,35]. The selection of the questions was made by consensus [36] of 2 researches who were expert shooting coaches with international experience and subsequently, two external international referees (one expert in qualitative methods and one expert in shooting sport) jointly reviewed the interviews until obtaining the final version of the interview script.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have suggested 20-min sessions of aerobic workouts with heart rates between 110 and 140 beats/minute or strength workouts with low loads and between 15 and 20 repetitions per set [12], while Rio [16] suggested aerobic sessions from 15 to 45 min with heart rates between 120 and 140 beats/minute and strength workouts between 12 and 20 repetitions per set with loads between 60% and 85% of the one maximum repetition (1RM). Regarding main motor abilities, strength [5,17], coordination [1], balance [18,19] and endurance [20] seem to be important physical capacities that affect shooting performance. Finger flexors or “hand grip” [21], deltoids abductor force [5], trapezius muscle [22], core and lower body muscles strength [23], seem to be the specific preferential musculature that determines shooting performance.…”
Section: Introductionmentioning
confidence: 99%